Improvements in the Microstructure and Mechanical Properties of Aluminium Alloys Using Ultrasonic-Assisted Laser Welding - Ahmed Teyeb; João Silva; Jamil Kanfoud; Phil Carr; Tat-Hean Gan; Wamadeva Balachandran (Metals, 2022)
Welding high-strength aluminium alloys is generally a delicate operation due to the degradation of mechanical properties in the thermally affected zone (TAZ) and the presence of porosities in the molten metal. Furthermore, aluminium alloys contain compounds that solidify before the rest of the base alloy, therefore acting as stress concentration points that lead to the phenomenon of hot cracking. This paper investigates the process of applying ultrasonic vibrations to the molten pool aluminium alloy AA6082 to improve both its microstructure and mechanical properties. We analysed conventional and ultrasonic-assisted laser welding processes to assess the sonication effect in the ultrasonic band 20–40 kHz. Destructive and nondestructive tests were used to compare ultrasonically processed samples to baseline samples. We achieved a 26% increase in the tensile and weld yield strengths of laser welds in the aluminium plates via the power ultrasonic irradiation of the welds under optimum ultrasonic variable values during welding. It is estimated that the ultrasound intensity in the weld melt, using a maximum power of 160 W from a pair of 28 kHz transducers, was 35.5 W/cm2 as a spatial average and 142 W/cm2 at the antinodes. Cavitation activity was significant and sometimes a main contributor to the achieved improvements in weld quality.